Symmetry-based IR group modes as dynamic probes of Nafion ion exchange site structure. (2nd September 2015) - Doan, Jonathan; Navarro, Nestor E.; Kumari, Dunesh; Anderson, Kierstyn; Kingston, Erin; Johnson, Cassandra; Vong, Andy; Dimakis, Nicholas; Smotkin, Eugene S.
Abstract: The categorization of Nafion side-chain IR group modes by exchange site local symmetry enables correlation of exchange site structure to state-of-hydration and ion exchange. During dehydration the Nafion-[H] exchange site transitions from the sulfonate to sulfonic acid form, corresponding to C3V and C1 symmetry, respectively: C3V, HF (1061 cm −1 ) and C3V, LF (969 cm −1 ) bands transition to C1, HF (1414 cm −1 ) and C1, LF (910 cm −1 ) bands. Metal ions (M) with ΔHhyd below 550 kJ/mol alter the exchange site at all states-of-hydration. They bind with C3V symmetry and exhibit high orbital overlap with the sulfonate sulfur and oxygen atoms. The Nafion-[H] C3V, LF (primarily sulfonate) vanishes at full dehydration with retention of the C3V, HF (primarily ether link). Theoretical Nafion-[M] C3V, LF bands (e.g., 940 cm −1 for Li + ) are not experimentally observed. Hydration waters of ions with ΔHhyd > 1800 kJ/mol cannot be displaced by sulfonate oxygens. Thus, the Nafion-[H] C3V, LF persists at all states of hydration. Graphical abstract: Highlights: FT-IR analysis of state-of-hydration and ion-exchange of Nafion exchange sites. Assignment of Nafion group modes in terms of exchange site local symmetry. Exchange site local symmetry of protonated Nafion depends on state-of-hydration. Correlation of cation hydration enthalpies to Nafion exchange site binding symmetry. Crystal orbital overlap population and DFT normal mode analysis of cation binding.